2009
DOI: 10.1111/j.2040-0209.2009.00324_2.x
|View full text |Cite
|
Sign up to set email alerts
|

Mobilising and Mediating Global Medicine and Health Citizenship: The Politics of AIDS Knowledge Production in Rural South Africa

Abstract: About IDSThe Institute of Development Studies is one of the world's leading organisations for research, teaching and communications on international development. Founded in 1966, the Institute enjoys an international reputation based on the quality of its work and the rigour with which it applies academic skills to real world challenges. Its purpose is to understand and explain the world, and to try to change it -to influence as well as to inform.IDS hosts five dynamic research programmes, five popular postgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…While his work reinforces the main claims made by Nguyen (2005) about the impact that an HIV diagnosis has in transforming a patient's subjectivities and in promoting activism, he remains critical of this concept, in particular in his more recent research with men (Robins, 2009a) and with HIV activists in rural areas of the Eastern Cape Province (Robins, 2009b). His earlier work (Robins, 2005) was conducted in rural and semi-urban areas in South Africa.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…While his work reinforces the main claims made by Nguyen (2005) about the impact that an HIV diagnosis has in transforming a patient's subjectivities and in promoting activism, he remains critical of this concept, in particular in his more recent research with men (Robins, 2009a) and with HIV activists in rural areas of the Eastern Cape Province (Robins, 2009b). His earlier work (Robins, 2005) was conducted in rural and semi-urban areas in South Africa.…”
Section: Introductionmentioning
confidence: 67%
“…In this regard Robins (2009b) showed that ART activists working in rural settings are subject to 'stiff opposition' from village actors as well as national state actors whom they attempt to recruit into the 'biopolitical projects and epistemic communities.' The resistance is manifest in the form of villagers rejecting scientific authority on HIV and the treatment communicated by the activists, in favour of embracing other explanations of HIV and AIDS and ill health in general -such as belief in witchcraft and the power of traditional medicines.…”
Section: Discussionmentioning
confidence: 99%
“…In this capacity, disclosure may lead to confrontations between activists and their peers, who prefer to deny their health needs as a way to maintain a 'strong' and 'independent' front. According to Robins (2009b), HIV treatment activists received harsh resistances from their communities when they attempted to change communal traditional beliefs about AIDS.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors note the role that for-eigners play in brokering relationships with transnational donors (Davis 2003) or how NGOs fulfill roles typically reserved for states before neoliberalism (Richard 2009). Local populations (Rossi 2006) as well as NGOs (Robins 2009a) were shown to have the ability to shift the contours of international aid. NGOs can be the "glue" to a fragmented neoliberalism (Schuller 2009) or the "friction" as groups across national and cultural boundaries interface (Tsing 2005).…”
Section: Ngos As Objects Of Anthropological Inquirymentioning
confidence: 99%
“…How does do-gooding relate to similar collective activity? One point of comparison could be that, whereas a social movement is expected to move, NGOs institutionalize: NGOs create projects (Freeman 2014;Lwijis 2009), write reports (Hodžić 2011), respond to auditors (Shore and Wright 2000;Strathern 2000), mediate contact (Robins 2009b;Schuller 2009), and so on. Even in this more focused discussion, it would be misguided to look for rigid criteria that must always be met.…”
Section: Ngo Research As Offering New Scope For Informing Theoreticalmentioning
confidence: 99%